Reviving lower body negative pressure as a countermeasure to prevent pathological vascular and ocular changes in microgravity - Katie M. Harris (Nature Portfolio, 2020)
Abstract Mitigation of spaceflight-related pathologies such as spaceflight-associated neuro-ocular syndrome (SANS) and the recently discovered risk of venous thrombosis must happen before deep space exploration can occur. Lower body negative pressure (LBNP) can simulate gravitational stress during spaceflight that is likely to counteract SANS and venous thrombosis, but the ideal dose and method of delivery have yet to be determined. We undertook a review of current LBNP literature and conducted a gap analysis to determine the steps needed to adapt LBNP for in-flight use. We found that to use LBNP in flight, it must be adapted to long time duration/low pressure use that should be compatible with crew activities. A lack of understanding of the etiology of the pathologies that LBNP can counteract hinders the application of LBNP as a countermeasure during spaceflight. Future research should aim at filling the knowledge gaps outlined in this review.